2016
DOI: 10.1016/j.juro.2015.12.068
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 Inflammasome Mediates Inflammation Produced by Bladder Outlet Obstruction

Abstract: Purpose While bladder outlet obstruction (BOO) is well-established to elicit an inflammatory reaction in the bladder that leads to overactive bladder and fibrosis, little is known about the mechanism by which this is initiated. Nod-Like Receptors (NLRs) and the structures they form (inflammasomes) have been identified as sensors of cellular damage (including pressure-induced damage) and triggers of inflammation. Recently, we identified these structures in the urothelium. In this study we assess the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 31 publications
1
82
0
Order By: Relevance
“…IL‐1β and IL‐18 are pro‐inflammatory cytokines which trigger the inflammatory response. We have shown in rats that an inhibitor of NLRP3, glyburide, not only blocks BOO‐induced inflammation but also the irritative voiding symptoms and downstream fibrosis . In this study, we explore a role for NLRP3‐mediated inflammation in triggering the denervation of the bladder that occurs following BOO .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…IL‐1β and IL‐18 are pro‐inflammatory cytokines which trigger the inflammatory response. We have shown in rats that an inhibitor of NLRP3, glyburide, not only blocks BOO‐induced inflammation but also the irritative voiding symptoms and downstream fibrosis . In this study, we explore a role for NLRP3‐mediated inflammation in triggering the denervation of the bladder that occurs following BOO .…”
Section: Introductionmentioning
confidence: 97%
“…However, over time symptoms progress toward bladder overactivity (increased frequency and urgency) and urge incontinence, defined as an irritative voiding pattern . Previous studies suggested that bladder inflammation underlies these irritative voiding symptoms . Although symptomatic relief is often possible with medications (alpha blockers, 5‐alpha reductase inhibitors, antimuscarinics, and β3‐agonists), these treatments do not fully alleviate the outflow resistance and the repeated physical/chemical insults associated with it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of BOO, administration of a NLRP3 inhibitor (glyburide) was shown to block inflammasome activation, reduce hypertrophy, and prevent inflammation (54). This may represent a pathway that can be targeted with treatment of symptoms induced by BOO, related to the inflammatory response and development of OAB symptoms.…”
Section: Biomarkersmentioning
confidence: 99%
“…NLRP3 is by far the best studied inflammasome and has been shown to respond to numerous DAMPs as well as PAMPs. Our lab has recently documented the presence of this NLR/ inflammasome (and several others) in the bladder urothelia [8] and its central role in two critical models of sterile inflammation (cyclophosphamide-induced hemmoragic cystitis and bladder outlet obstruction) [9,10]. Among the list of PAMPS that activate this inflammasome (directly or indirectly), lipopolysaccharide (LPS) is one of the most potent virulence factors of uropathogens [11].…”
Section: Introductionmentioning
confidence: 99%